IMPACT OF CASE BASED DISCUSSION AS AN INSTRUCTIONAL TOOL ON THE ANNUAL EXAMINATION RESULTS IN OPHTHALMOLOGY FOR FOURTH YEAR UNDERGRADUATE MEDICAL STUDENTS: Case Based Discussion - Nasir, Jamshed; Ashar, Abid; Ahmad, Amina; Khanum, Afshan (Pakistan Armed Forces Medical Journal, 2018)
Objective: Determine the effectiveness of case-based discussion (CbD) in terms of annual professional ophthalmology examination performances (scores) at undergraduate level involving students. Study Design: Quasi experimental study. Place and Duration of Study: FMH College of Medicine and Dentistry for under graduate 4th year MBBS class in Ophthalmology (13 months‟ duration), from Dec 2013 to Dec 2014. Material and Methods: After approval from the IRB, scores of the historical control group, consisting of all 4th year MBBS students from previous four years included (64, 89, 96 and 85 respectively) were collected, who underwent traditional teaching. A total of 113 students were enrolled using non-probability convenience sampling technique in the interventional group of the study, who were exposed to CbD. Their scores in the annual university examination were collected in the subject of ophthalmology. The data was analyzed for its normalcy and Mann Whitney test was applied for comparison. Scores of both groups were correlated using pearson‟s coefficient of correlation to determine similarity of constructs measured through traditional assessment method and CbD. Results: There was statistically insignificant difference (p-value 0.087) between scores obtained by historical controls and those who received intervention (CbD). There was insignificant negative correlation in (-0.028) between scores obtained through traditional assessment and CbD. Conclusion: CbD fosters higher order thinking among undergraduate students in Ophthalmology. However, traditional assessment methods do not measure constructs that should be evaluated among undergraduate students, urging formal evaluation of the assessment items for further improvement.